PENERAPAN FUNGSI TONGKONAN DALAM MENINGKATKAN KEMAMPUAN MEMBACA DAN BERHITUNG SISWA SEKOLAH DASAR DI LEMBANG TONDON - Marchelina Rante; Yulianus Marampa’ Rombeallo; Dina Ramba; Novalia Sulastri; Hendrik Hendrik (Indonesian Collaboration Journal of Community Services, 2023)
Tongkonan is a traditional house located in the Toraja area, precisely in the mountainous area of ??the northern part of South Sulawesi. Tongkonan is shaped like a boat facing north. Tongkonan is a special building erected by a community leader or a family clump where Tongkonan has a special function in society which is not only used as a house for community leaders, but also functions as a guardian of various rules in Aluk Todolo that regulate social life, beliefs and Toraja culture. Tongkonan also has a very deep philosophical meaning for the Toraja people. Based on observations made by the team, there are still many students at Lembang Tondon Elementary School who do not understand and are fluent in reading and arithmetic, at their current age, they should have understood and understand reading and arithmetic. so that the team carried out teaching activities for elementary school students about reading, counting and drawing the types of carvings and understanding the meaning of the carvings which were carried out at Tongkonan Tella. From the results of these activities which were carried out for approximately 2 months, it was clear that the development of these children, who previously had not been able to distinguish letters, were now able to spell little by little. In addition, children who previously had not been able to sort numbers properly and correctly, are now able to sort and even can do addition and subtraction well